The role of crowding out pursuit of fiscal policy and the case of the Greek economic crisis - Theodoropoulos, Sotirios (SPOUDAI Journal of Economics and Business, 2010)
The issue of the crowding out of fiscal policy advises than an increase in government debt reaching high levels, reduces national saving, raises interest rates, crowds out private investment and reduces future output. On this issue is mainly centered the controversy between monetarists and Keynesians, debated for many years. Also, substantial empirical research has been devoted testing the crowding out of private economic activity by public economic activity, focusing on the validity of Ricardian equivalence hypothesis. By this paper we explore the channels and mechanisms through which this phenomenon takes place, also its arising consequences under EMU’s environment and strongly affected fiscal policy framework. We also consider this as a proper theoretical instrument, suitable for in vestigation in the case of current greek economic crisis, where the private sector faces a severe and multidimensional crowding out by public sector. JEL Classifications: E43, E62, E63, H63.